2001
DOI: 10.1039/b100835h
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse potentiometric imaging of active filiform corrosion using a scanning Kelvin probe technique

Abstract: The kinetics and mechanism of filiform corrosion occurring on polymer coated AA2024-T3 aluminium alloy are investigated using a scanning Kelvin probe technique (SKPT). Repeated scanning by SKPT is used to generate a time-lapse animation showing the dynamic evolution of localised free corrosion potential (E corr ) patterns. E corr values in the head region of propagating filaments are up to 150 mV lower that the intact polymer coated surface, indicating local depassivation. However, E corr values in the filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…1, 3, and 4 are consistent with chloride-induced substrate depassivation 25 and anodic attack occurring through Reaction 2 [4][5][6][7]21 Al…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1, 3, and 4 are consistent with chloride-induced substrate depassivation 25 and anodic attack occurring through Reaction 2 [4][5][6][7]21 Al…”
Section: Discussionsupporting
confidence: 77%
“…21 Initially, continuous regions of decreased E corr , consistent with local surface depassivation, became evident in the immediate vicinity of the penetrative defect. After a period, which we refer to as the initiation time (t 0 ), these continuous regions of depassivation became fragmented to form individual filament heads observed to move normal to and away from the coating defect, i.e., travelling parallel with the substrate rolling direction.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…With the help of SKP, Williams et al [9] showed that the outward migration of hydroxide ions in the electric field alongside the interface stopped inward migration of cerium cations from the defect, while the cerium cations from the dispersed silica and bentonite in the PVB coating reached the active sites and effectively inhibited coating delamination. Williams et al also successfully applied SKP in the study of filiform corrosion [10].…”
Section: Introductionmentioning
confidence: 99%
“…The scanning Kelvin probe (SKP), which has a lateral resolution of about 50 µm, has been used to map the spatial and temporal distribution of Volta potential distributions beneath a thin-film electrolyte or underneath a coating. [9][10][11][12][13][14][15][16][17] The delamination front on steel was characterized by a steep change in Volta potential (500 mV). The intact interface had a high potential plateau associated with oxygen reduction, and the delaminated region exhibited lower potentials.…”
Section: Fontana Corrosion Center Department Of Materials Science Anmentioning
confidence: 99%